The appearance of whale shark (Rhincodon typus) in Kwatisore Waters, Nabire District, Central Papua Province - Punusingon, Olfie; Dananjaya, Wayan Kantun; Rapi, Nuraeni L. (Acta Aquatica: Aquatic Sciences Journal, 2024)
The appearance of whale sharks (Rhincodon typus) is related to the availability of food in certain waters and is a tourist attraction so integrated management is needed so that they do not become a threat to whale sharks. Whale sharks appear regularly and take place throughout the year with the largest number of individuals only occurring in Kwatisore waters. This study aims to examine the bioecology of whale sharks, which is related to appearance based on individuals, number and time of appearance and sex. Primary data collection was carried out from January to March 2023, using the census method on 4 charter fishing gear units anchored in Kwatisore waters. The results showed that 21 individuals of whale sharks appeared with a total of 225 appearances in January, 245 appearances in February and 248 appearances in March and there was one new individual who migrated into Kwatisore waters with ID number 184. Whale sharks appear mostly in the morning with a percentage of 100% with a total length ranging from 3 to 7.5 m.Keywords: Appearance; New Individuals; Whale Sharks